Organisational cynicism and self-efficacy predicting professionalism among teachers in Oyo State, Nigeria - Okurame, David E; Aniezie, Maria U; Uye, Emmanuel E (Social Sciences, Humanities and Education Journal (SHE Journal), 2024)
The 21st century teachers have been affected by globalization, technological innovation and diversity in workplace thus affecting their professionalism. Teachers who develop unconcern attitudes and suffer neglect are likely to have their performance at work affected. Therefore, this study examined organizational cynicism and self-efficacy as predictors of professionalism among teachers in Oyo State, Nigeria. Cross-sectional survey design was adopted while purposive sampling technique was used to select one Local Government Area for the study. Data were collected from 300 teachers using validated scales and analysed using t-test of independent means and multiple regressions analysis to test three hypotheses at a p < 0.05 level of significance. The result revealed that organizational cynicism and self-efficacy significantly influenced professionalism among teachers. Also, organizational cynicism and self-efficacy jointly and independently predicted professionalism among teachers. Finally, organizational cynicism and self-efficacy independently predicted professionalism among study participants. The study concluded that organisational cynicism and self-efficacy are strong predictors of professionalism among teachers. Therefore, government agencies and other stakeholders should work together to improve teachers’ professional skills.